Laboratorium Moderne : Bildende KUnst, Fotografie und Film im Aufbruch - Köb, Edelbert; Bogner, Dieter; Faber, Monika; Fischer-Briand, Roland; Fritz, Elisabeth; Fuchs, Rainer; Grissemann, Stefan; Kernbauer, Eva; Neuburger, Susanne; MUMOK, Wien (Wien : MUMOK (Museum Moderner Kunst Stiftung Ludwig) Wien, 2007)
Arp, Hans (Jean) ; Balla, Giacomo ; Baumeister, Willi ; Bayer, Herbert ; Belling, Rudolf ; Bellmer, Hans ; Bergmann-Michel, Ella ; Blossfeldt, Karl ; Bortnyik, Sándor ; Brancusi, Constantin ; De Chirico, Giorgio ; d'Ebneth, Lajos ; Derain, André ; Dexel, Walter ; Dicker, Friedl ; van Doesburg, Theo ; Drahomir Ruzicka, Josef ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Ernst, Max ; Fautrier, Jean ; Giacometti, Alberto ; Gleizes, Albert ; González, Julio ; Gris, Juan ; Gropius, Walter ; Gutfreund, Otto ; Hausmann, Raoul ; Henri, Florence ; Itten, Johannes ; Joostens, Paul ; Kandinsky, Wassily ; Kassak, Lajos ; Kiesler, Friedrich ; Klee, Paul ; Klien, Erika Giovanna ; Kupka, Frantisek ; Laurens, Henri ; Leger, Fernand ; Lipchitz, Jacques ; Magritte, René ; Man Ray ; Mansouroff, Paul ; Marcoussis, Louis ; Masson, Andre ; Miro, Joan ; Moholy, Lucia ; Moholy-Nagy, Laszlo ; Mondriaan, Piet ; Nähr, Moritz ; Oppenheim, Meret ; Outerbridge, Paul ; Ozenfant, Amédée ; Pevsner, Antoine ; Picabia, Francis ; Picasso, Pablo ; Pomassl, Franz ; Renger-Patzsch, Albert ; Richter, Hans ; Rietveld, Gerrit ; Sander, August ; Schlemmer, Oskar ; Schwitters, Kurt ; Servranckx, Victor ; Soutter, Louis ; Stegemeyer, Elfriede ; Steichen, Edward J. ; Stern, Alexander ; Taeuber-Arp, Sophie ; Vertov, Dziga ; Wagner, Otto ; Wolff, Paul ; Zadkine, Ossip
Laboratorium Moderne : Bildende Kunst, Fotografie und Film im Aufbruch, MUMOK, Wien, 23.03 - 07.10.2003
boek
Keywords: Wien